The Impact of Tax Avoidance and National In-Country Value Certification (ICV) on Corporate Sustainability - Rabboua, Mukhlesa; Diab, Rania; Alzayani, Latifa; ElKelish, Walaa Wahid; Al Ali, Amel Ibrahim; Al Mulla, Adil (International Review of Management and Marketing, 2025)
This paper investigates the impact of tax avoidance and National In-Country Value (ICV) certification on corporate sustainability in the emerging market of the United Arab Emirates. An explanatory study was conducted using the inductive approach. Quantitative data was collected using a survey instrument distributed to senior accountants. The findings show a neutral relationship between tax avoidance and corporate sustainability. Respondents show a significant impact of hard laws on tax avoidance. In addition, respondents perceive a significant relationship between ICV and corporate sustainability in the UAE emerging market. Respondents’ nationality, age, education, and company characteristics, including size, type, and activity, determine the relationships between tax avoidance, soft laws, hard laws, ICV, and sustainability practices. The National In-Country Value (ICV) certification represents an innovative tool to boost local economic development and growth. Thus, this paper provides valuable guidance for managers, accountants, regulators, and policymakers to improve corporate and national sustainability policies.